2023
DOI: 10.1038/s41598-023-42536-w
|View full text |Cite
|
Sign up to set email alerts
|

Using artificial intelligence algorithms to reconstruct the heat transfer coefficient during heat conduction modeling

Elzbieta Gawronska,
Maria Zych,
Robert Dyja
et al.

Abstract: The article shows the usage of swarming algorithms for reconstructing the heat transfer coefficient regarding the continuity boundary condition. Numerical calculations were performed using the authors’ own application software with classical forms of swarm algorithms implemented. A functional determining error of the approximate solution was used during the numerical calculations. It was minimized using the artificial bee colony algorithm (ABC) and ant colony optimization algorithm (ACO). The considered in pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Based on preliminary research [20,21,22], it was found that both ABC and ACO optimization algorithms achieve good results in reconstructing the heat conduction coefficient of the separation layer. Now, the authors are asking if increasing the population size makes sense and what impact it might have on the final results.…”
Section: Introductionmentioning
confidence: 99%
“…Based on preliminary research [20,21,22], it was found that both ABC and ACO optimization algorithms achieve good results in reconstructing the heat conduction coefficient of the separation layer. Now, the authors are asking if increasing the population size makes sense and what impact it might have on the final results.…”
Section: Introductionmentioning
confidence: 99%
“…The Bees algorithm is another important optimization technique for solving heat transfer problems. Bozorgan et al improved the geometrical characteristics of a shell and tube heat exchanger (tube length, baffle spacing, tube internal and outer diameters, shell diameter, and pitch size) to maximize the heat transfer coefficient while minimizing overall pressure loss. They increased the heat transfer coefficient by 23% and reduced the overall pressure drop by 2% compared to the original shell and tube heat exchanger.…”
Section: Introductionmentioning
confidence: 99%